2022
DOI: 10.3389/fchem.2022.1011186
|View full text |Cite|
|
Sign up to set email alerts
|

Colloidal nanomaterials for water quality improvement and monitoring

Abstract: Water is the most important resource for all kind forms of live. It is a vital resource distributed unequally across different regions of the globe, with populations already living with water scarcity, a situation that is spreading due to the impact of climate change. The reversal of this tendency and the mitigation of its disastrous consequences is a global challenge posed to Humanity, with the scientific community assuming a major obligation for providing solutions based on scientific knowledge. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 187 publications
0
4
0
Order By: Relevance
“…However, due to its low solubility and propensity to aggregate, pristine graphene poses difficulties in the treatment of wastewater. To overcome these limitations, researchers have worked on the synthesis of similar compounds, for example, graphene oxide (GO) and graphite-like nanoplatelets (GNP) . Further, graphene-based adsorbents are accompanied by several other challenges such as the production and utilization of these adsorbents in wastewater treatment may involve energy-intensive processes, influencing overall energy consumption.…”
Section: Innovative Materials For Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to its low solubility and propensity to aggregate, pristine graphene poses difficulties in the treatment of wastewater. To overcome these limitations, researchers have worked on the synthesis of similar compounds, for example, graphene oxide (GO) and graphite-like nanoplatelets (GNP) . Further, graphene-based adsorbents are accompanied by several other challenges such as the production and utilization of these adsorbents in wastewater treatment may involve energy-intensive processes, influencing overall energy consumption.…”
Section: Innovative Materials For Wastewater Treatmentmentioning
confidence: 99%
“…To overcome these limitations, researchers have worked on the synthesis of similar compounds, for example, graphene oxide (GO) and graphite-like nanoplatelets (GNP). 98 Further, graphenebased adsorbents are accompanied by several other challenges such as the production and utilization of these adsorbents in wastewater treatment may involve energy-intensive processes, influencing overall energy consumption. Second, achieving long-term stability and durability of graphene-based adsorbents in harsh wastewater conditions poses a challenge, given the susceptibility of graphene materials to degradation over time, impacting their adsorption capacity.…”
Section: Innovative Materials For Wastewater Treatmentmentioning
confidence: 99%
“…In the past few years, surface-enhanced Raman scattering (SERS) spectroscopy has been explored as a powerful tool in water quality monitoring due to its ability to detect trace levels of several contaminants, including pesticides and pharmaceuticals. [6][7][8][9][10][11] The SERS technique relies on the interaction of analyte molecules with metal surfaces, particularly those of gold and silver colloids, which greatly amplify the Raman signal, enabling the detection of low analyte concentrations. 12,13 The SERS effect is the result of the contribution of two mechanisms: the electric field enhancement due to the metal surface (electromagnetic mechanism) and the chemical interaction, namely charge transfers, of the analyte molecules with the metal surface (chemical mechanism).…”
Section: Introductionmentioning
confidence: 99%
“…Along with the advances in environmental research, in the past few years, several authors have suggested nanomaterials to enhance primary and advanced water treatment [ 9 ]. Due to its small size and, consequently, high surface and reactive areas, the use of nanomaterials enables the improvement of several properties compared to bulk material [ 9 ]. More recently, two-dimensional (2D) nanomaterials have gained importance.…”
Section: Introductionmentioning
confidence: 99%